Pelatihan Teknis Pembuatan Filter Air Bertekanan Rendah bagi Masyarakat Desa Kedungrandu Kecamatan Patikraja Kabupaten Banyumas - Muhammad Sehah (Universitas Jenderal Soedirman, 2020)
Technical training on manufacturing low pressure water filter for community of Kedungrandu Village, Patikraja District, Banyumas Regency has been done in April – July 2017. The background of this activity is the presence of pollution in the community wells water that allegedly due to intrusion of liquid waste resulted from decomposition process of organic waste at the landfill of Gunung Tugel, Kedungrandu Village. The objective of this activity is to do socialization and technical training of manufacture the low pressure water filter to treat the well water which been contaminated into water that feasible to be consumed based on the physics parameter. While the expected benefits of this activity is be obtained the well water which clean, clear, hygienic, and feasible to be consumed for people that living in the area around of the TPA Gunung Tugel. After the technical training activity has been done, the largely participants give some positively response on this activity and there are their desire to implement and disseminate it. The average attainment index of this activity successfulness that based on the observation results utilizes quiz is 85.16%; with the highest index is 92.19% (for item of support to the technical training activity with topics like the above as effort to add knowledge) and the lowest index is 77.34%% (for item of able to understand the material of PKM that been tought by the team of lecturers nicely). The understanding and mastery of participant of the activity to the technical training matters that given have rather good, although still needs improved again. It can be known from the recapitulation results of pre-test and post-test values, where the average of the pre-test value is 3.375; and while the average of the post-test value is 7.178. Thus there is the ascension from the pre-test value up to the post-test value is about of 112.70%. Although the cost is relatively cheap, the realization of the water filter manufacturing is also lacking, due limited funds and no special fund support from the village government